miR2118-dependent U-rich phasiRNA production in rice anther wall development - Saori Araki (Nature Portfolio, 2020)
MicroRNA2118 induces the production of phased small interfering RNAs (phaisRNAs) in plants. Here the authors show that rice miR2118 is required for both male and female fertility and supports the production of atypical U-rich 21 nt phasiRNAs that are abundant in anther walls.